Drugst: One - a plug-and-play solution for online systems medicine and network-based drug repurposing - Maier, Andreas; Hartung, Michael; Abovsky, Mark; Adamowicz, Klaudia; Bader, Gary D; Baier, Sylvie; Blumenthal, David B; Chen, Jing; Elkjaer, Maria L; Garcia-Hernandez, Carlos; Helmy, Mohamed; Hoffmann, Markus; et al. (Nucleic acids research, 2024)
In recent decades, the development of new drugs has become increasingly expensive and inefficient, and the molecular mechanisms of most pharmaceuticals remain poorly understood. In response, computational systems and network medicine tools have emerged to identify potential drug repurposing candidates. However, these tools often require complex installation and lack intuitive visual network mining capabilities. To tackle these challenges, we introduce Drugst.One, a platform that assists specialized computational medicine tools in becoming user-friendly, web-based utilities for drug repurposing. With just three lines of code, Drugst.One turns any systems biology software into an interactive web tool for modeling and analyzing complex protein-drug-disease networks. Demonstrating its broad adaptability, Drugst.One has been successfully integrated with 21 computational systems medicine tools. Available at https://drugst.one, Drugst.One has significant potential for streamlining the drug discovery process, allowing researchers to focus on essential aspects of pharmaceutical treatment research.
Veröffentlicht: 23 May 2024
Gesehen am 09.12.2024